Last‐Passage Algorithm for Charge Distribution Over a Finite Region. Issue 2 (14th January 2021) - Jang, Hoseung; Given, James; Yu, Unjong; Hwang, Chi‐Ok
Abstract: First‐passage and last‐passage Monte Carlo algorithms have been used for computing charge distribution on a conducting object. First‐passage algorithms are used for an overall charge distribution on a conducting object and Given–Hwang's last‐passage algorithms are used for a charge density at a specific point on a flat or spherical surface of a conductor. In this paper, a last‐passage algorithm for computing charge distribution over a finite region of a conducting object is presented. Abstract : First‐ and last‐passage Monte Carlo algorithms have been used for computing charge distribution on a conducting object. First‐passage algorithms are used for an overall charge distribution and Given‐Hwang's last‐passage algorithms for a charge density at a specific point on the conducting object. Here, we present a last‐passage algorithm for computing charge distribution over a finite region of the conducting object.